Model kemitraan lembaga pendidikan nonformal dalam penyelenggaraan pendidikan anak usia dini - Kartini Marzuki; M. Ali Latif Amri (Seminar Nasional LP2M UNM, 2019)
The general objective of this study is to reveal the partnership model of non-formal education in the implementation of early childhood education. This research is qualitative research that seeks to explore deeply the stages in establishing partnerships as well as supporting and inhibiting factors for partnership implementation among non-formal educational institutions. Informants in this study were the head of the Panre Tanrara ECD Center, integrated service post manager and Toddler Family Development and a community leader. To test the validity of the research data, triangulation was used both in the form of source triangulation and methods. The results of the study indicate that the partnership model undertaken by non-formal education institutions in delivering early childhood education is a Topdown partnership model. Where the World Bank as the organizing center designs and forms partnerships since PAUD centers are formed by forming and directly involving integrated service posts and Toddler Family Development as partners. Posyandu provides health services to children, Bina Keluarga Balita (BKB) as an organizer of parenting programs for childcare and PAUD as providers of education services for early childhood. The supporting factors for implementing the partnership are systematic planning, the availability of educated staff and the environmental conditions of the institutions that support the implementation of partnerships